2021
DOI: 10.1097/01.aoa.0000796200.17421.fe
|View full text |Cite
|
Sign up to set email alerts
|

Immediate “Kangaroo Mother Care” and Survival of Infants With Low Birth Weight

Abstract: patients who were confirmed with COVID-19 postoperatively (20.4%) compared with preoperatively (9.1%). Care and staffing needs differ, so preoperative COVID-19 testing and diagnoses can be helpful to ensure needs are met before complications arise. Strategies can be implemented to address more emergent surgeries where prior testing is not feasible. When making discussions, the mother, neonate, and HCWs should be considered to minimize risk and improve safety for all involved. Future research and studies should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 0 publications
1
44
0
4
Order By: Relevance
“…While a Cochrane review (2016) showed that KMC initiated after clinical stabilization reduces mortality by 40% [6], evidence of the effect of initiating KMC immediately after birth without waiting for babies to become stable was unavailable until recently. This research question was addressed by a multicountry, randomized, controlled trial (iKMC study) co-ordinated by WHO [14]. This trial was conducted in five hospitals in Ghana, India, Malawi, Nigeria, and Tanzania.…”
Section: Kangaroo Mother Care and Low-birth-weight Newbornsmentioning
confidence: 99%
See 4 more Smart Citations
“…While a Cochrane review (2016) showed that KMC initiated after clinical stabilization reduces mortality by 40% [6], evidence of the effect of initiating KMC immediately after birth without waiting for babies to become stable was unavailable until recently. This research question was addressed by a multicountry, randomized, controlled trial (iKMC study) co-ordinated by WHO [14]. This trial was conducted in five hospitals in Ghana, India, Malawi, Nigeria, and Tanzania.…”
Section: Kangaroo Mother Care and Low-birth-weight Newbornsmentioning
confidence: 99%
“…In the iKMC study, the median daily duration of skin-to-skin contact in the neonatal intensive care unit was 16.9 h (interquartile range, 13.0 to 19.7) in the MNCU and 1.5 h (interquartile range, 0.3 to 3.3) in the conventional NICU [14].…”
Section: Prolonged Continuous Effective Kmcmentioning
confidence: 99%
See 3 more Smart Citations